2022
DOI: 10.1038/s43247-022-00606-3
|View full text |Cite
|
Sign up to set email alerts
|

Eruption chronology of the December 2021 to January 2022 Hunga Tonga-Hunga Ha’apai eruption sequence

Abstract: The 15 January 2022 eruption of Hunga Tonga-Hunga Ha’apai, and the preceding eruptions on 19 December 2021 and 13 January 2022, were remarkable, partly because the eruptions generated extensive umbrella clouds, regions where the volcanic clouds spread laterally. Here we use satellite remote sensing to evaluate the umbrella cloud tops’ heights, longevities, water contents, and volumetric flow rates. We identified two umbrella clouds at distinct elevations on 15 January 2022. Specifically, after 05:30 UTC, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 56 publications
8
26
0
1
Order By: Relevance
“…Phase 2 encompasses the most intense stage of the eruption from 04:00-07:11, with mass eruption rates (flux of magma, magmatic gas, and vaporized seawater) exceeding 5 × 10 9 kg s −1 from 04:15-04:57 based on the rate of umbrella growth (Text S3, Figure S4 in Supporting Information S1). The plume rose to a maximum overshoot of 58 km and expanded into at least two atmospheric levels, as noted by Carr et al (2022) and Gupta et al (2022). The upper umbrella intruded into the stratosphere (reaching 30-40 km and higher) while a second, lower cloud spread out at the level of the tropopause (but with cloud tops reaching ∼20 km).…”
Section: Chronology Of Eruptive Activity On 15 Januarymentioning
confidence: 78%
See 1 more Smart Citation
“…Phase 2 encompasses the most intense stage of the eruption from 04:00-07:11, with mass eruption rates (flux of magma, magmatic gas, and vaporized seawater) exceeding 5 × 10 9 kg s −1 from 04:15-04:57 based on the rate of umbrella growth (Text S3, Figure S4 in Supporting Information S1). The plume rose to a maximum overshoot of 58 km and expanded into at least two atmospheric levels, as noted by Carr et al (2022) and Gupta et al (2022). The upper umbrella intruded into the stratosphere (reaching 30-40 km and higher) while a second, lower cloud spread out at the level of the tropopause (but with cloud tops reaching ∼20 km).…”
Section: Chronology Of Eruptive Activity On 15 Januarymentioning
confidence: 78%
“…An explosive eruption began on 19 December 2021 (coordinated universal time, UTC) near the remote islands of Hunga Tonga and Hunga Ha'apai in the South Pacific Ocean (Carn et al., 2022; Gupta et al., 2022). These two islands are small peaks on the rim of a much larger submarine caldera volcano known as Hunga Volcano (Taaniela Kula, Tonga Geological Services, written communication, 10 September 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The first is in the context of volcanological research, where improved predictions of the umbrella cloud growth may improve the inference of eruption source parameters from volcanic plume observations. Umbrella cloud diameter has been used directly to infer the volume flux at neutral buoyancy level (e.g., Bear‐Crozier et al., 2020; Gupta et al., 2022; Hargie et al., 2019; Pouget et al., 2016), most commonly using the scaling law and circular umbrella cloud assumption of Woods and Kienle (1994). The parametrization presented here may improve the accuracy of such inferences, and allow them to be made where the umbrella cloud is significantly wind‐affected.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 13, 2023. ; https://doi.org/10.1101/2023.04.11.536409 doi: bioRxiv preprint destroy most of the vent communities in a given region (see the recent eruption of the submarine volcano Hunga Tonga -Hunga Ha'apai in December 2021, Gupta et al, 2022). In a recent study of Gigantidas haimaensis mussels from cold seep ecosystems in the South China Sea, Shi et al (2022) found that male gonads contained oocytes (while female gonads did not contain spermatocytes).…”
Section: A Unique Pair Of Xy Chromosomes Across the Three Species?mentioning
confidence: 99%